Original articleImmunoexpression of gemins 2 and 4 in the rat spinal cord. Is the SMN complex a new target in investigations of sporadic amyotrophic lateral sclerosis pathogenesis? - Rafałowska, Janina; Sulejczak, Dorota; Gadamski, Roman; Dziewulska, Dorota (Folia Neuropathologica, 2012)
Sporadic amyotrophic lateral sclerosis (sALS) is a neurodegenerative disease leading to degeneration and loss of motoneurons in different structures of the nervous system. Although aetiology of the disease is unknown, it is hypothesized that the survival motor neuron (SMN) protein which protects motoneurons in spinal muscular atrophy, may play a similar role in ALS. Relatively little is known about normal expression and functions of the SMN complex compounds, i.e. SMN protein and the related gemins. Therefore, we have decided to examine the physiological expression of SMN and gemins 2 and 4 in spinal cords of healthy Wistar rats at different age using immunofluorescence and immunohistochemical methods. Our study revealed that (1) in rat spinal cord neurons, the immunoexpression of SMN and gemins 2 and 4 is present through the whole animal lifespan although the reactive cells reveal different intensity of the immunolabeling, (2) both SMN and gemin 2, and SMN and gemin 4 are present in the same motoneurons, (3) immunoexpression of gemin 2 and 4 decreases slightly with aging.